1998
DOI: 10.1007/s007050050412
|View full text |Cite
|
Sign up to set email alerts
|

Beak and feather disease virus and porcine circovirus genomes: intermediates between the geminiviruses and plant circoviruses

Abstract: Circoviruses are a diverse group of animal and plant pathogens with undefined relationships to one another but for their non-geminate, non-enveloped capsids and circular, single-stranded DNA genomes. The sequences of the beak and feather disease virus and porcine circovirus genomic DNAs are presented and analyzed in the context of the other members of the family. Sequence comparisons, inferred phylogenies, and geographic occurrence suggest that the ambisense circoviruses, particularly the beak and feather dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
161
0
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(169 citation statements)
references
References 42 publications
3
161
0
5
Order By: Relevance
“…CAV, PBFD virus and porcine circovirus. Yet recent DNA cloning and sequencing studies have described striking similarities between porcine circovirus and Pigeon circovirus infection 155 PBFD virus genomes (Niagro et al, 1998), whereas no such homologies were found when these two viruses were compared with CAV (Bassami et al, 1998). The pigeon circovirus has been described as antigenically distinct from PBFD virus, although possible homologous DNA sequences, as demonstrated by DNA in situ hybridization, have been found between both viruses (Woods et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAV, PBFD virus and porcine circovirus. Yet recent DNA cloning and sequencing studies have described striking similarities between porcine circovirus and Pigeon circovirus infection 155 PBFD virus genomes (Niagro et al, 1998), whereas no such homologies were found when these two viruses were compared with CAV (Bassami et al, 1998). The pigeon circovirus has been described as antigenically distinct from PBFD virus, although possible homologous DNA sequences, as demonstrated by DNA in situ hybridization, have been found between both viruses (Woods et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Circoviruses are tiny non-enveloped icosahedral viruses (15-24 nm in diameter) with a single-stranded circular DNA of 1.76 kb to 2.31 kb (Bassami et al, 1998;Niagro et al, 1998). Like most other members of the newly proposed Circoviridae family, PiCV is characterized by typical basophilic globular inclusions in light microscopy (Woods et al, 1993;Shivaprasad et al, 1994;Woods et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…While several small stem-loop structures were conserved in the full-length genomes, there was no apparent conserved nonanucleotide sequence or surrounding repetitive sequences. However, similar to circoviruses capsid proteins, the amino terminus of ORF1 possesses a high number of arginine residues (Niagro et al, 1998 ;Mushahwar et al, 1999). Thus, the TT virus ORF1 product may have DNA-binding activity and function in packaging of the viral genome.…”
Section: Discussionmentioning
confidence: 99%
“…The causative agent, PBFD virus (PBFDV), is a nonenveloped icosahedral DNA virus with a diameter of 14-17 nm (2,18,32). It carries single-stranded circular DNA with a complete genome size of about 2 kb (2,18,32).…”
mentioning
confidence: 99%